The effect of visfatin rs2110385 gene polymorphism over oral antidiabetic drug response (Annals of Medical Research, 2021)
Aim: The aim of our study is to investigate the effects of rs2110385 polymorphism of the visfatin gene on obesity in Turkish study groups. The rs2110385 polymorphism was analyzed in terms of genotype frequencies, obesity-related parameters, demographic data, serum visfat-in levels and drug use in obese and non-obese subjects.Materials and Methods: The PCR-RFLP method was used to determine the visfatin gene rs2110385 genotype. MicroELISA method was used to measure serum visfatin levels.Results: Homozygous wild type (G / G), heterozygous (G / T) and homozygous polymor-phic (T / T) genotype frequencies of the visfatin gene rs2110385 polymorphism was found to be respectively as, 54.1%, 66.7%, 61.8% in obese and 45.9%, 33.3%, 38.2% in non-obese. There was no statistical difference between the groups in terms of genotype frequen-cies and serum visfatin levels. Homozygous wild type genotype frequency was higher than heterozygous and homozygous polymorphic genotype in obese group with type 2 diabetes mellitus using sulfonylurea and glinide, respectively. The rs2110385 mutation reduced the response to antidiabetics in obese patients with type 2 diabetes mellitus.Conclusions: In conclusion, our results may indicate that obese type 2 diabetic patients with the visfatin gene T / T rs2110385 genotype may benefit more efficiently from oral an-tidiabetic drugs other than glinide or sulfonylurea.
Keywords: Glinide; obesity; rs2110385 polymorphsim; sulphonylurea; visfatin